A study of the level of professional image of future foreign language teachers in Ukrainian universities - Yuliia Nenko; Tetiana Sytnik; Olena Orlova (Universidade Federal do Norte do Tocantins, 2020)
The article addresses the problem of development of the professional image of a foreign language teacher in Ukraine. The present study was contemplated to ascertain the attitude of university students in Ukraine towards the studied notion and reveal the level of its formation. The structure of the professional image of future foreign language teachers consist of several underlying constructs which have been described in the paper: cognitive, axiological and operational components. Results show that Ukrainian teachers-to-be held different perceptions to the notion of professional image of a foreign language teacher. The purpose of this survey is to provide suggestion of organizational, personal and pedagogical conditions to facilitate the development of professional image of future foreign language teachers in Ukrainian higher education institutions.